Quality of Life After Poor-Grade Aneurysmal Subarachnoid Hemorrhage. Issue 5 (4th May 2023) - Goldberg, Johannes; Z'Graggen, Werner J.; Hlavica, Martin; Branca, Mattia; Marbacher, Serge; D'Alonzo, Donato; Fandino, Javier; Stienen, Martin N.; Neidert, Marian C.; Burkhardt, Jan-Karl; Regli, Luca; Seule, Martin; et al.
Abstract : BACKGROUND: Poor-grade aneurysmal subarachnoid hemorrhage (aSAH) is associated with high mortality and poor disability outcome. Data on quality of life (QoL) among survivors are scarce because patients with poor-grade aSAH are underrepresented in clinical studies reporting on QoL after aSAH. OBJECTIVE: To provide prospective QoL data on survivors of poor-grade aSAH to aid clinical decision making and counseling of relatives. METHODS: The herniation World Federation of Neurosurgical Societies scale study was a prospective observational multicenter study in patients with poor-grade (World Federation of Neurosurgical Societies grades 4 & 5) aSAH. We collected data during a structured telephone interview 6 and 12 months after ictus. QoL was measured using the EuroQoL - 5 Dimensions - 3 Levels (EQ-5D-3L) questionnaire, with 0 representing a health state equivalent to death and 1 to perfect health. Disability outcome for favorable and unfavorable outcomes was measured with the modified Rankin Scale. RESULTS: Two hundred-fifty patients were enrolled, of whom 237 were included in the analysis after 6 months and 223 after 12 months. After 6 months, 118 (49.8%) patients were alive, and after 12 months, 104 (46.6%) patients were alive. Of those, 95 (80.5%) and 89 (85.6%) reached a favorable outcome with mean EQ-5D-3L index values of 0.85 (±0.18) and 0.86 (±0.18). After 6 and 12 months, 23 (19.5%) and 15 (14.4%) of those alive had an unfavorable outcome with mean EQ-5D-3L index values of 0.27 (±0.25) and 0.19 (±0.14). CONCLUSION: Despite high initial mortality, the proportion of poor-grade aSAH survivors with good QoL is reasonably large. Only a minority of survivors reports poor QoL and requires permanent care. Abstract :